Treatment and Outcome of Osteoporotic Thoracolumbar Vertebral Fractures With Anterior or Posterior Tension Band Failure (OF 5): Short-Term Results From the Prospective EOFTT Multicenter Study. Issue 1 (April 2023) - Osterhoff, Georg; Schenk, Philipp; Katscher, Sebastian; Schnake, Klaus John; Bäumlein, Martin; Zimmermann, Volker; Schmeiser, Gregor; Scherer, Michael A.; Müller, Michael; Sprengel, Kai; Liepold, Katja; Schramm, Simon; et al.
Study Design: Subgroup analysis of a multicenter prospective cohort study Objective: To analyse surgical strategies applied to osteoporotic thoracolumbar osteoporotic fracture (OF) 5 injuries with anterior or posterior tension band failure and to assess related complications and clinical outcome. Methods: A multicenter prospective cohort study (EOFTT) was conducted at 17 spine centers including 518 consecutive patients who were treated for an osteoporotic vertebral fracture (OVF). For the present study, only patients with OF 5 fractures were analysed. Outcome parameters were complications, Visual Analogue Scale (VAS), Oswestry Disability Questionnaire (ODI), Timed Up & Go test (TUG), EQ-5D 5L, and Barthel Index. Results: In total, 19 patients (78 ± 7 years, 13 female) were analysed. Operative treatment consisted of long-segment posterior instrumentation in 9 cases and short-segment posterior instrumentation in 10 cases. Pedicle screws were augmented in 68 %, augmentation of the fractured vertebra was performed in 42%, and additional anterior reconstruction was done in 21 %. Two patients (11 %) received short-segment posterior instrumentation without either anterior reconstruction or cement-augmentation of the fractured vertebra. No surgical or major complications occurred, but general postoperative complications were observed in 45%. At a follow-up of mean 20 ± 10 weeks (range, 12 to 48 weeks), patients showed significant improvements in all functional outcome parameters. Conclusions: In this analysis of patients with type OF 5 fractures, surgical stabilization was the treatment of choice and lead to significant short-term improvement in terms of functional outcome and quality of life despite a high general complication rate.